Factor in Predicting Psychological Well-being in Late Adolescents - Jirathikrengkrai, Chutima; Vongsirimas, Nopporn; Thanoi, Wareerat; Phetrasuwan, Supapak (Nursing Science Journal of Thailand, 2021)
Purpose: This research aims to study the predictive power of perceived stress, resilience, social support, and coping strategies (problem-focused coping and emotional-focused coping) on psychological well-being in late adolescents. Design: Predictive study. Methods: Participants were 490 students with 10th to 12th grades in government schools in Bangkok. The instruments used in data collection consisted of personal information form, Ryff’s Psychological Well-Being Scale, Perceived Stress Scale, Connor-Davidson Resilience Scale, Multidimensional Scale of perceived social support, and the Brief COPE inventory. Data were analyzed by multiple linear regression. Main findings: The study results showed that perceived stress, resilience, social support, and coping strategies (problem-focused coping and emotional-focused coping) could predict psychological well-being in late adolescents with statistical significance and all factors could account for 63% of the variance explained in psychological well-being (R2 = .63). Conclusion and recommendations: All study factors were statistically significant predictors of psychological well-being in late adolescents. The study results can be used as the basis for activities to promote mental well-being in late adolescents through promoting the stress management skill and activities that help increase social support awareness.